Drug-resistant bacteria in the critically ill: patterns and mechanisms of resistance and potential remedies - Karukappadath, Riaz M.; Sirbu, Dumitru; Zaky, Ahmed (Frontiers in Antibiotics, 2023)
Antimicrobial resistance in the intensive care unit is an ongoing global healthcare concern associated with high mortality and morbidity rates and high healthcare costs. Select groups of bacterial pathogens express different mechanisms of antimicrobial resistance. Clinicians face challenges in managing patients with multidrug-resistant bacteria in the form of a limited pool of available antibiotics, slow and potentially inaccurate conventional diagnostic microbial modalities, mimicry of non-infective conditions with infective syndromes, and the confounding of the clinical picture of organ dysfunction associated with sepsis with postoperative surgical complications such as hemorrhage and fluid shifts. Potential remedies for antimicrobial resistance include specific surveillance, adequate and systematic antibiotic stewardship, use of pharmacokinetic and pharmacodynamic techniques of therapy, and antimicrobial monitoring and adequate employment of infection control policies. Novel techniques of combating antimicrobial resistance include the use of aerosolized antibiotics for lung infections, the restoration of gut microflora using fecal transplantation, and orally administered probiotics. Newer antibiotics are urgently needed as part of the armamentarium against multidrug-resistant bacteria. In this review we discuss mechanisms and patterns of microbial resistance in a select group of drug-resistant bacteria, and preventive and remedial measures for combating antibiotic resistance in the critically ill.